MEMS-based in-situ tensile experiments designed to arrest catastrophic failure in brittle nanomaterials. (November 2020) - Ahn, Daehyeok; Kim, Dae-Gon; Lee, Hansuek; Jang, Dongchan
Abstract: Quantitative characterization of mechanical properties of many nano- or micro-scaled materials is of crucial importance for many technological applications. Among various experimental methods, the in-situ nanomechanical tensile testing is of particular significance due to its capability of direct observation of mechanical behavior. Especially, the tensile loading mode enabling the precise displacement control is desirable for brittle nanomaterials that often suffer from the catastrophic failure by mechanical instability. In this study, we developed the MEMS-based nanomechanical tensile device optimized for stable displacement control even in the presence of the rapid reduction of sample stiffness. The MEMS device is designed to stabilize the motion of the actuating rod in the testing equipment via the high stiffness of springs and the large mass of the movable part. To verify the performance of the device, we conducted tensile testing on the pre-notched metallic glass samples and successfully observed fast load drops during crack propagation.